The Caring Attitude of Nurses and Mother’s Motivation for Child Immunization Attendance - Pardede, Jek Amidos; Simamora, Mathalena; Irwan, Farhana (Talenta Publisher, 2020)
Nurses’ caring attitude is the core in nursing standard practices that is mandatory for all nurses. In practicing caring attitudes, nurses show their empathy and care to patients in order to positively affect patients’ healing process. Furthermore, caring attitudes by nurses to mothers are expected to increase mothers’ motivation to attend to child immunization at public health centers regularly. The objective of the study was to identify the relationship between nurses’ caring attitude and the motivation of mothers in regularly taking their children for immunization at Belawan Public Health Center. This study employed correlational descriptive method using cross sectional approach. A total number of 52 mothers with the children of 0-12 months old served as research population. Sampling technique was total sampling technique in this study. By performing spearman rank statistical test, it was obtained that there was a strong correlation between caring attitude of nurses and mothers’ motivation for child immunization attendance (p= 0.005; r= 0.551). It is concluded that caring attitude of the nurses improve the motivation of mothers for child immunization attendance. It is suggested that nurses should practice caring while serving mother patients in order to increase awareness and internal motivation among mothers to bring their children to Public Health Center for immunization. Keywords: caring attitude of nurses; mothers’ motivation; immunization attendance.